KOMUNIKASI EFEKTIF SEBAGAI PARADIGMA BARU PENGELOLAAN RISIKO KONSUMEN DALAM CREATIVE MANAGEMENT SYSTEM MOODLE - Hefri Yodiansyah; Nanik Yuzalmi Nanik (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
Analysis of Business Marketing Strategies on the "RAFE" Element with Main Performance Evaluation Analysis on "RNNs" with Activity Logs "CMCNs." The results found business opportunities for success at the core of the entrepreneurial organization's communication goals that were supported knowing communication literacy using the MMS "CMS" Creative Management System method to analyze information technology literacy with competency required business opportunities. Business learning is understood as the process of business communication as a narrative communication method developed by postmodern. Management studies on promotion (creative) on the thinking patterns of small business creativity (talent management). The role of the Medium Enterprises Creative Community (MSME) is agreed with the cooperation contract as a very important financial capital in the national financial system. The role of entrepreneurship especially business opportunities in aspects of the pattern of the communication environment, such as increasing employment opportunities, equality, increasing resources, developing the creative economy and increasing the attractiveness of advertising through communication promotion. Digital literacy interests, attitudes, and abilities of individuals using digital technology as a process of communication objectives to access, manage, integrate, analyze, evaluate information data, build new knowledge, create and communicate with others, so they can participate effectively. In the first discussion, Marketing Communication Mix. Second, Creative Marketing System "CMS," Third, Perception of the business environment, Fourth, Strategic Ecological and Fifth, Cultural Patterns and Social Environment.